#### Answer

81

#### Work Step by Step

$(xy+1)^2$ $\longrightarrow$ substitute
=$(2(-5)+1)^2$ $\longrightarrow$ resolve expression in parenthesis
=$(-10+1)^2$
=$(-9)^2$
=$81$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

81

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.